Download presentation

Presentation is loading. Please wait.

Published byJeremiah York Modified over 3 years ago

1
Rearranging algebraic Formulae for GCSE Mathematics © David Weeks www.mathsmadeeasy.co.uk Use mouse click after each slide

2
Things to remember: Dont rush it. You must go through each stage of your method and not try to skip any. If you are making x the subject it means that you want to end up with x= and this is the only x in your answer. Whatever you do to one side of the equals sign you must do to the other.

3
Example1 H=8e + 2, Make e the subject of the formulae Lets see how we got H... in H=8e + 2 Do the exact opposite to get e.. We get H Start with e Multiply all by 8 x8 Add 2 +2 We get e Divide all by 8 ÷8 Subtract 2 -2 Start with H So e=(H-2)÷8 or e= (H-2) 8 Your turn: Make a the subject of the formula F=6a +5 © David Weeks

4
Example 2 V=7(c+9)+ 10, Make c the subject of the formulae Lets see how we got V... In V=7(c+9)+10 Do the exact opposite to get c.. Start with c Add 9 +9 Multiply all by 7 x7 We get V Add 10 +10 We get c Minus 9 -9 Divide all by 7 ÷7 Start with V Minus 10 -10 So c=(V-10)÷7 -9 or c= (V-10) - 9 7 Your turn: Make z the subject of the formula F=6(z+9) + 8 © David Weeks

5
Example 3 T=(s+4) 2 + 3, Make s the subject of the formulae Lets see how we got T... In T=(s+4) 2 +3 Do the exact opposite to get s.. Start with s Add 4 +4 Squared all ( ) 2 We get T Add 3 +3 We get s Minus 4 -4 Square root all Start with T Minus 3 -3 Your turn: Make p the subject of the formula F=(p+9) 2 + 8 So s=(T-3) -4 or s= (T-3) - 4 © David Weeks

6
Example 4 Lets see how we got X... Do the exact opposite to get Y.. Start with Y Add 5 +5 Divide all by 7 ÷7 We get X minus 6 -6 We get Y Minus 5 -5 Multiply all by 7 x7 Start with X Add 6 +6 So Y=(X+6)x7 -5 or Y=7(X+6) - 5 X =(Y+5) - 6, Make Y the subject of the formulae 7 Your turn: Make g the subject of the formula F= (g+9) - 7 5 © David Weeks

7
Example 5 T=4(u 2 +7), Make w the subject of the formulae Lets see how we got T... In T=4(u 2 +7) Do the exact opposite to get w.. Start with u Square it u 2 Add 7 +7 We get T Multiply all by 4 x4 We get u Minus 7 -7 Square root All Start with T Divide by 4 ÷ 4 Your turn: Make p the subject of the formula F=5(p 2 + 8) So u=(T÷4 -7) or u= T – 7 4 © David Weeks

8
Answers 1. Make a the subject of the formula F=6a +5 2. Make z the subject of the formula F=6(z+9) + 8 3. Make p the subject of the formula F=(p+9) 2 + 8 5. Make p the subject of the formula F=5(p 2 + 8) 4. Make g the subject of the formula F= (g+9) - 7 5 a=(F-5)÷6 or a= (F-5) 6 z=(F-8)÷6 -9 or z= (F-8) - 9 6 So p=(F-8) -9 or p= (F-8) - 9 g=(F+7)x5 -9 or g=5(F+7) - 9 So p=(F÷5 -8) or p= F – 8 5 Restart © David Weeks

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google